Let7b-5p is Upregulated in the Serum of Emirati Patients with Type 2 Diabetes and Regulates Insulin Secretion in INS-1 Cells - Aljaibeji, Hayat; Elemam, Noha Mousaad; Mohammed, Abdul Khader; Hasswan, Hind; Thahyabat, Mahammad Al; Alkhayyal, Noura; Sulaiman, Nabil; Taneera, Jalal (Experimental and Clinical Endocrinology & Diabetes, 2020)
Let7b-5p is a member of the Let-7 miRNA family and one of the top expressed miRNAs in human islets that implicated in glucose homeostasis. The levels of Let7b-5p in type 2 diabetes (T2DM) patients or its role in β-cell function is still unclear. In the current study, we measured the serum levels of let7b-5p in Emirati patients with T2DM (with/without complications) and control subjects. Overexpression or silencing of let7b-5p in INS-1 (832/13) cells was performed to investigate the impact on insulin secretion, content, cell viability, apoptosis, and key functional genes. We found that serum levels of let7b-5p are significantly (p<0.05) higher in T2DM-patients or T2DM with complications compared to control subjects. Overexpression of let7b-5p increased insulin content and decreased glucose-stimulated insulin secretion, whereas silencing of let7b-5p reduced insulin content and secretion. Modulation of the expression levels of let7b-5p did not influence cell viability nor apoptosis. Analysis of mRNA and protein expression of hallmark genes in let7b-5p transfected cells revealed a marked dysregulation of Insulin, Pancreatic And Duodenal Homeobox 1 (PDX1), glucokinase (GCK), glucose transporter 2 (GLUT2), and INSR. In conclusion, an appropriate level of let7b-5p is essential to maintain β-cell function and may be regarded as a biomarker for T2DM.
Keywords: Diabetes; Autoimmunity; Let7b-5p.; INS-1 (832/31); miRNA